Percurso da escrevivência em Mulher Mat(r)iz, de Miriam Alves - Carneiro, Luciana Priscila Santos (2019)
While confronting the white hegemonic system, Afro-Brazilian writers noticed – within the black movement itself – some resistance to the recognition and to the specificities of their writings. The writability (escrevivência) – expression created by Conceição Evaristo, and adopted by Miriam Alves in order to describe her writing – breaks the walls of prejudices that walk side by side, such as gender and ethnicity. It also assigns specificity to the expression of the black female body in writing, and occupies the rightful place of black women in literature and in epistemology. This work aims to investigate how the writability and the aesthetic and ideological paths covered by this epistemology are created in order to entangle the stories of Mulher Mat(r)iz (2011), written by Miriam Alves. In this way, we explore sociological, cultural and literary studies: African memory, ethnicity, female body, social classes and economic positions, violence, language and receptivity. Therefore, we consider necessary to research the history and the contexts which produce the Afro-Brazilian Literature of female authorship. It is also important to consider its dialogues with black feminism and with the social and individual questions that black women experience in Brazilian society. In our analysis, we collect statements from some representatives of the Afro-Brazilian literature of female authorship, such as Miriam Alves, Conceição Evaristo and Lívia Natália. In addition, the discussion is supported by the theorists Constância Lima Duarte (2010), Eduardo de Assis Duarte (2014), Maria Nazareth Fonseca (2002), among others that write about Afro-Brazilian writings, black women expressions and their experiences.